2007
DOI: 10.1016/j.mam.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienols in health and disease: The other half of the natural vitamin E family

Abstract: Tocochromanols encompass a group of compounds with vitamin E activity essential for human nutrition. Structurally, natural vitamin E includes eight chemically distinct molecules: alpha-, beta-, gamma- and delta-tocopherol; and alpha-, beta-, gamma- and delta-tocotrienol. Symptoms caused by alpha-tocopherol deficiency can be alleviated by tocotrienols. Thus, tocotrienols may be viewed as being members of the natural vitamin E family not only structurally but also functionally. Palm oil and rice bran oil represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
207
1
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(217 citation statements)
references
References 163 publications
2
207
1
7
Order By: Relevance
“…Although TRF has been shown to have numerous beneficial effects on human health (Sen et al, 2007), it was not effective in preventing or minimising stress-induced changes in the dentate gyrus of rats in this study.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Although TRF has been shown to have numerous beneficial effects on human health (Sen et al, 2007), it was not effective in preventing or minimising stress-induced changes in the dentate gyrus of rats in this study.…”
Section: Discussioncontrasting
confidence: 55%
“…In vivo oral supplementation of tocotrienol has been demonstrated to protect rats against stroke-induced injury (Khanna et al, 2005). Furthermore, tocotrienol exerts neuroprotective activity against various chemical insults, such as glutamate, homocysteic acid and linoleic acid (Sen et al, 2000;Khanna et al, 2006;Sen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these studies suggest that α-TTP-KO mice offer an in vivo model for identifying molecular and cellular mechanisms relevant to human CNS pathological changes that occur with aging and that may be ameliorated by dietary antioxidants like α-T. The model may also have utility in testing neuroprotective effects of other members of vitamin E family such as tocotrienols (Sen et al, 2007) An understanding of the role of α-TTP in brain would be aided by relating α-T levels in the α-TTP-KO mice with biochemical parameters. Yokota et.al (Yokota et al, 2001) have shown that α-T is very low in two brain regions and that the levels reached quantifiable levels only after feeding a diet high in vitamin E. To characterize the role of α-TTP gene in the retention, distribution and biological actions of α-T in the CNS, we have determined α-T, cholesterol, total glutathione and the expression of α-TTP gene from several brain regions.…”
Section: Introductionmentioning
confidence: 96%
“…In addition to vitamin E action, tocopherols are known as antioxidants due to their chromanol ring [2,3], which affords an anti-inflammatory effect that reduces the risk of cardiovascular disease [4,5]. Recently, tocotrienols have been reported to show unique physiological characteristics, such as hypocholesterolemic, anticancer, antidiabetic, neuroprotective, hepatoprotective, and nephron-protective effects [6][7][8]. Rice bran oil containing vitamin E nutrients has been shown to significantly suppress hyperlipidemic responses in diabetic rats through the hypocholesterolemic effect of these ingredients [9,10].…”
Section: Introductionmentioning
confidence: 99%